Pathways of flower infection and pollen-mediated dispersion of Pseudomonas syringae pv. actinidiae, the causal agent of kiwifruit bacterial canker. Issue 1 (December 2018) - Donati, Irene; Cellini, Antonio; Buriani, Giampaolo; Mauri, Sofia; Kay, Callum; Tacconi, Gianni; Spinelli, Francesco
Abstract Flowers can provide a protected and nutrient-rich environment to the epiphytic microflora, thus representing a sensible entry point for pathogens such asPseudomonas syringae pv.actinidiae (Psa). This bacterium can colonize both male and femaleActinidia flowers, causing flower browning and fall, and systemic invasion of the host plant, eventually leading to its death. However, the process of flower colonization and penetration into the host tissues has not yet been fully elucidated. In addition, the presence of Psa in the pollen from infected flowers, and the role of pollination in the spread of Psa requires confirmation. The present study employed a Psa strain constitutively expressing the fluorescent GFPuv protein, to visualize in vivo flower colonization. Microscopy observations were performed by means of confocal laser scanning and wide-field fluorescent microscopy, and were coupled with the study of Psa population dynamics by quantitative PCR (q-PCR). The pathogen was shown to colonize stigmata, move along the stylar furrow, and penetrate the receptacles via the style or nectarhodes. Once the receptacle was invaded, the pathogen migrated along the flower pedicel and became systemic. Psa was also able to colonize the anthers epiphytically and endophytically. Infected male flowers produced contaminated pollen, which could transmit Psa to healthy plants. Finally, pollinators (Apis mellifera andBombus terrestris ) were studied in natural conditions, showing that, although they can be contaminated with Psa, the pathogen's transmission via pollinators is contrasted by its short survival in the hive. Kiwi fruit: Insights to combat bacterial canker Studying the transmission pathways of a bacterium that infects and kills kiwi fruit plants suggests that modified plant protection strategies could minimize the risk of disease. Researchers in Italy and New Zealand, led by Francesco Spinelli at the University of Bologna, investigatedPseudomonas syringae pv. Actinidiae (Psa), which causes kiwi fruit bacterial canker. This has been a major problem worldwide since a pandemic outbreak in 2008. The results show that flower tissues, especially the stigmata which receive transmitted pollen, are crucial sites allowing Psa to grow and penetrate into the plants. Evidence is presented of bacterial transmission via the pollen dispersed from plants that do not themselves show signs of infection. Suggested new control strategies include inspecting and treating pollen-donating plants, and using biological agents to compete with Psa growing inside kiwi fruit flowers.